Tumor Growth Remains Refractory to Myc Ablation in Host Macrophages - Riley J. Morrow; Amr H. Allam; Josh Konecnik; David Baloyan; Christine Dijkstra; Moritz F. Eissmann; Saumya P. Jacob; Megan O’Brien; Ashleigh R. Poh; Matthias Ernst (Cells, 2022)
Aberrant expression of the oncoprotein c-Myc (Myc) is frequently observed in solid tumors and is associated with reduced overall survival. In addition to well-recognized cancer cell-intrinsic roles of Myc, studies have also suggested tumor-promoting roles for Myc in cells of the tumor microenvironment, including macrophages and other myeloid cells. Here, we benchmark Myc inactivation in tumor cells against the contribution of its expression in myeloid cells of murine hosts that harbor endogenous or allograft tumors. Surprisingly, we observe that LysMCre-mediated Myc ablation in host macrophages does not attenuate tumor growth regardless of immunogenicity, the cellular origin of the tumor, the site it develops, or the stage along the tumor progression cascade. Likewise, we find no evidence for Myc ablation to revert or antagonize the polarization of alternatively activated immunosuppressive macrophages. Thus, we surmise that systemic targeting of Myc activity may confer therapeutic benefits primarily through limiting Myc activity in tumor cells rather than reinvigorating the anti-tumor activity of macrophages.